The file on Rosemount creek - Howes, Jim; Vanzet, Gaston (Macmillan Education Australia Pty Ltd: Australia, 2009)
"Dean Matthews and Ahmed Massouf live in the tiny country town of Rosemount Creek. Several members of the community have observed strange things in the skies over their town, but their effort to get the government interested in the sightings are frustrated by a general disbelief. However, when the government agents finally come to the town, they begin to see what might really be happening..."
Keywords: English, Fiction